Malta : 2017 Article IV Consultation-Press Release; Staff Report. (IMF Staff Country Reports; Country Report, 2018)
This 2017 Article IV Consultation highlights that Malta's economic growth remains one of the strongest in Europe, owing to favorable economic conditions and sound policies, which advanced structural reforms and supported the strengthening of private and public balance sheets. Output is estimated to have expanded by 6.8 percent in 2017, accompanied by dynamic job creation, which brought unemployment to a record low. Strong inflows of foreign workers and rising labor force participation kept wage pressures contained in most sectors, thus contributing to low inflation despite a positive output gap. The outlook is favorable, with growth decelerating gradually and converging to about 3 percent over the medium term.